The Role of Information Technology in Visual Communication: Analysis of Graphic Displays in Live Football Matches on Television - Rahmat Edi Irawan; Merry Fridha Tri Palupi; Arleen Ariestyani; Trisna Prandawa Putra; Attanan Tachopilsawong (P3M Politeknik Negeri Media Kreatif, 2026)
This study examines how information technology shapes visual communication through broadcast graphics in live football television. It compares selected graphic displays from the 2026 FIFA World Cup Asian Qualifiers and the UEFA Champions League, including line-up boards, score graphics, small scoreboards, and offside/VAR displays. Using qualitative visual communication analysis, the study applies Gillian Rose's framework by examining the sites of production, image, and audiencing through technological, compositional, and social modalities. The findings show that broadcast graphics function not only as decorative overlays but also as production infrastructure, data visualization tools, and interpretive interfaces for audiences. UEFA Champions League graphics emphasize premium branding, dynamic composition, and integrated data presentation, whereas Asian Qualifiers graphics prioritize clarity, authority, and functional information delivery. The study contributes to media and communication scholarship by positioning football broadcast graphics as communicative artifacts shaped by technology, institutional branding, and popular-cultural value. Practically, it offers insights for Indonesian broadcasters seeking to improve international-standard sports production.